2022
DOI: 10.14309/ajg.0000000000002022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prediction Models for Pancreatic Cancer in General and At-Risk Populations: A Systematic Review

Abstract: Identifying high-risk individuals using a risk prediction model could be a crucial first stage of screening pathways to improve the early detection of pancreatic cancer. A systematic review was conducted to critically evaluate the published primary literature on the development or validation of clinical risk prediction models for pancreatic cancer risk. METHODS:MEDLINE, Embase, and Web of Science were searched for relevant articles from the inception of each database up to November 2021. Study selection and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…In our multivariable logistic regression models, the significant risk variables were as follows: non-modifiable-male gender and age, genetic predisposition-non-O blood type and a higher PRS quintile (Q4 vs. Q1, OR = 1.67; Q5 vs. Q1, OR = 2.03), lifestyle-related modifiable variables-current smokers and higher alcohol consumption, and medical history-related variables-pancreatitis, DM, and cholecystitis, cholelithiasis, or cholecystectomy. In previously published studies, a number of logistic regression models [20,21, were built to explore pancreatic cancer risks. Of them, nine models [20,53,56,57,[62][63][64]66,68] were developed in the general population, and others were created in populations with DM history or clinical gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our multivariable logistic regression models, the significant risk variables were as follows: non-modifiable-male gender and age, genetic predisposition-non-O blood type and a higher PRS quintile (Q4 vs. Q1, OR = 1.67; Q5 vs. Q1, OR = 2.03), lifestyle-related modifiable variables-current smokers and higher alcohol consumption, and medical history-related variables-pancreatitis, DM, and cholecystitis, cholelithiasis, or cholecystectomy. In previously published studies, a number of logistic regression models [20,21, were built to explore pancreatic cancer risks. Of them, nine models [20,53,56,57,[62][63][64]66,68] were developed in the general population, and others were created in populations with DM history or clinical gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple models [21] that have been published associated with PaCa risk prediction. However, each model concentrated only on selected risk variables, such as symptoms-based, genetic-based, or lifestyle-related.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond familial pancreatic cancer, the most well-recognized risk factor for pancreatic tumor is smoking, followed by chronic pancreatitis, diabetes, and obesity, specifically high body-mass index (BMI) and centralized fat distribution [105][106][107][108][109][110][111][112][113][114].…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition, another subgroup of familial pancreatic tumor is due to germline mutations in ATM [94][95][96][97][98][99][100][101][102][103][104]. Beyond familial pancreatic cancer, the most well-recognized risk factor for pancreatic tumor is smoking, followed by chronic pancreatitis, diabetes, and obesity, specifically high body-mass index (BMI) and centralized fat distribution [105][106][107][108][109][110][111][112][113][114].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several observational cohort studies have suggested an antineoplastic effect of metformin. Diabetes and chronic pancreatitis alone are associated with an increased risk of pancreatic cancer (with an especially high risk if both are present) and are integral parts of clinical prediction models for pancreatic cancer [ 22 ]. Therefore, any effect of metformin to prevent pancreatic cancer would be of great value.…”
Section: Classical Therapiesmentioning
confidence: 99%